Applications of statistics and probability in civil engineering - International Conference on Applications of Statistics and Probability in Civil Engineering (2011 : Zurich, Switzerland); Faber, Michael H.; Kohler, Jochen; Nishijima, Kazuyoshi (Leiden, The Netherlands : CRC Press, 2011)
Includes bibliographical references and index